Analisis Determinan Tingkat Kemiskinan di Pulau Madura Tahun 2015- 2023 - Istiyani, Nanik; Latifah, Khusnul; Yuliati, Lilis (Akuntansi & Ekonomika, 2024)
This research aims to analyze the direct and indirect influence of the Human Development Index, Open Unemployment Rate, and Regency Minimum Wage on Poverty Levels on Madura Island. The data used in this research is a type of secondary data sourced from the Central Statistics Agency. The analytical method used is Multiple Linear Regression with panel data on the island of Madura for 9 years from 2015 to 2023. Based on the results of the analysis it is known that the Human Development Index has a negative and insignificant effect on the level of poverty, the Open Unemployment Rate has a positive and significant effect on the level of poverty, and the Regency Minimum Wage have a negative and insignificant effect on the poverty level.